METHODOLOGY AND EFFECTIVENESS OF TEACHING THE RUSSIAN LANGUAGE TO PRESCHOOL CHILDREN (American Journal of Research in Humanities and Social Sciences, 2023)
This article describes the methodology of teaching Russian language for preschool children. In addition, it is said that the Russian language, like English, is becoming a world language, so it should be taught from preschool age, that is, from kindergarten age.